1987
DOI: 10.1002/aja.1001790205
|View full text |Cite
|
Sign up to set email alerts
|

Splenic hypertrophy and extramedullary hematopoiesis induced in male Syrian hamsters by short photoperiod or melatonin injections and reversed by melatonin pellets or pinealectomy

Abstract: Adult male Syrian hamsters either placed in a short photoperiod alone or kept in a long photoperiod and given daily afternoon injections of the pineal indole melatonin (25 micrograms) exhibited splenic hypertrophy and extramedullary hematopoiesis in addition to a marked regression in testicular weight. The testicular regression as well as the changes in spleen weight and histology could be prevented if the animals in short photoperiod were either pinealectomized or implanted subcutaneously with a pellet contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 20 publications
1
27
0
Order By: Relevance
“…Here the artificial shortening of day lengths or alternatively melatonin injections induce an increase in thymus weight [49] and spleen hypertrophy [50], implying a melatonin-mediated photoperiodic effect on the immune system. Furthermore, it was demonstrated that melatonin controls diurnal and seasonal rhythms of leukocyte proliferation [51], of cytokine production [44,45] and NK cell activity [52] in mammalian bone marrow cells.…”
Section: Neuro-endocrine Melatonin: Systemic Effects Of Pineal Melatomentioning
confidence: 98%
“…Here the artificial shortening of day lengths or alternatively melatonin injections induce an increase in thymus weight [49] and spleen hypertrophy [50], implying a melatonin-mediated photoperiodic effect on the immune system. Furthermore, it was demonstrated that melatonin controls diurnal and seasonal rhythms of leukocyte proliferation [51], of cytokine production [44,45] and NK cell activity [52] in mammalian bone marrow cells.…”
Section: Neuro-endocrine Melatonin: Systemic Effects Of Pineal Melatomentioning
confidence: 98%
“…Melatonin treatment affects the reproductive capacity, the production of sex hormones, and certain immune functions [47, 48], suggesting the involvement of the hypothalamus-pituitary axis in these responses. However, in our study we did not find significant differences between the responses to treatment in girls and boys, discarding a sex-dependent effect of the immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, melatonin appears to coordinate many seasonal and daily changes in energy use and energy conservation [70] [111,114] [ 144] and Syrian hamsters (Mesocricetus auratus) [25]. Splenic masses, total splenic lymphocyte numbers and macrophage counts were significantly higher in hamsters exposed to short photoperiod as compared to animals exposed to long photoperiod [25,142]. Photoperiod did not affect thymic weight or antibody production in hamsters [24] [ 14].…”
mentioning
confidence: 99%